2013
DOI: 10.1039/c3cp50540e
|View full text |Cite
|
Sign up to set email alerts
|

Screening of transition and post-transition metals to incorporate into copper oxide and copper bismuth oxide for photoelectrochemical hydrogen evolution

Abstract: A new dispenser and scanner system is used to create and screen Bi-M-Cu oxide arrays for cathodic photoactivity, where M represents 1 of 22 different transition and post-transition metals. Over 3000 unique Bi : M : Cu atomic ratios are screened. Of the 22 metals tested, 10 show a M-Cu oxide with higher photoactivity than CuO and 10 show a Bi-M-Cu oxide with higher photoactivity than CuBi2O4. Cd, Zn, Sn, and Co produce the most photoactive M-Cu oxides, all showing a 200-300% improvement in photocurrent over CuO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
71
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 60 publications
3
71
0
Order By: Relevance
“…The film thickness is approximately 2 μm (Figure S8 in the Supporting Information) and is highly compacted indicating its strong adhesion to the FTO electrode surface that is achieved by involving Mim in the preparation. X‐ray photoelectron spectroscopy (XPS, Figure S9 in the Supporting Information) measurements of the p‐CuBi 2 O 4 film showed the presence of Cu 2p 3/2 and Bi 4f 5/2 and 4f 7/2 peaks at 934.1, 163.8, and 158.5 eV, respectively . The energy‐dispersive spectroscopy (EDS) measurements (Figure S10 in the Supporting Information) confirmed the presence of Cu and Bi and O in the film.…”
Section: Figurementioning
confidence: 83%
See 1 more Smart Citation
“…The film thickness is approximately 2 μm (Figure S8 in the Supporting Information) and is highly compacted indicating its strong adhesion to the FTO electrode surface that is achieved by involving Mim in the preparation. X‐ray photoelectron spectroscopy (XPS, Figure S9 in the Supporting Information) measurements of the p‐CuBi 2 O 4 film showed the presence of Cu 2p 3/2 and Bi 4f 5/2 and 4f 7/2 peaks at 934.1, 163.8, and 158.5 eV, respectively . The energy‐dispersive spectroscopy (EDS) measurements (Figure S10 in the Supporting Information) confirmed the presence of Cu and Bi and O in the film.…”
Section: Figurementioning
confidence: 83%
“…These include electrodeposition/thermala nnealing method, [42,45,46] screen printing, [52] and drop-casting/heating method. [53] We recently developed a simple novel method involving an ethyl methyli midazolium triflate (EMI OTf) ionic liquid to prepare ah ighly mechanically stable thin film of water oxidation anode (CaMn-Oxide [54] )o r photoanode (BiVO 4 [55] )o nt he surface of FTO electrode. EMI OTf, however,i se xpensive and the need to replace it with a cheaper material is in high demand.…”
mentioning
confidence: 99%
“…However,i ti sa lso observed that doping is not alwaysf avorable to enhance the water-splitting properties, as it can also become ar ecombination center. [162] Although the photocurrentc an be greatlye nhanced by doping with ad esired metal ion, the stabilityi ssue remains ac ritical challenge for PEC performance. Surprisingly,e xcept for BiVO 4 ,r eports on doping of metals or non-metals for other bismuth-based materials are rare.…”
Section: Co-catalysts and Dopingmentioning
confidence: 99%
“…Generally, high spatial resolution and ultrafast spectroscopy are not needed in these studies, and the reader is referred to other literature on the topic. 12,15,16,[23][24][25][26][27][28] The remainder of this paper provides an overview of in situ SPM techniques (Section 2), ultrafast spectroscopy techniques (Section 3), and computational tools (Section 4) that have been used, or have the potential to be used, for in situ investigation photoelectrodes with high spatial and/or temporal resolution. In addition to describing the basic principles behind each class of techniques, the opportunities and challenges for using these…”
Section: Introductionmentioning
confidence: 99%